2020
DOI: 10.3390/rs12244039
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of High-Density UAV Point Clouds for the Measurement of Young Forestry Trials

Abstract: The measurement of forestry trials is a costly and time-consuming process. Over the past few years, unmanned aerial vehicles (UAVs) have provided some significant developments that could improve cost and time efficiencies. However, little research has examined the accuracies of these technologies for measuring young trees. This study compared the data captured by a UAV laser scanning system (ULS), and UAV structure from motion photogrammetry (SfM), with traditional field-measured heights in a series of forestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 92 publications
(162 reference statements)
1
15
0
Order By: Relevance
“…This result is nevertheless consistent with recent findings reported by Ref. [26]. Whether this is a general phenomenon or other DAP algorithms/software packages and parameter settings would produce substantially different results is unknown and out of the scope of the current study.…”
Section: Influence Of Tree Size and Tree Species On Tree Height Modelingsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is nevertheless consistent with recent findings reported by Ref. [26]. Whether this is a general phenomenon or other DAP algorithms/software packages and parameter settings would produce substantially different results is unknown and out of the scope of the current study.…”
Section: Influence Of Tree Size and Tree Species On Tree Height Modelingsupporting
confidence: 93%
“…In an assessment of UAS 3D point clouds from laser and DAP for individual tree height estimation over tree plantations with an average tree height of 2.6 m, Ref. [26] reported that DAP underestimated height to a greater extent than laser and that the accuracy was greater for laser than for DAP. However, their 3D data had an exceptionally high point density (443-939 points m −2 for DAP and 325-649 points m −2 for laser), which makes comparisons with previous findings based on data from airborne platforms and coarser resolution imagery difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…., n}, respectively. Under the premise of minimizing the error function error(G, p) between the two point sets in formula (8), the least squares method can be adopted to iteratively perform the optimal coordinate transform and calculate the rotation matrix and translation matrix until the preset error threshold or maximum number of iterations is reached:…”
Section: Computational Intelligence and Neurosciencementioning
confidence: 99%
“…Large-scale, standardized breeding can effectively improve the output and profit of pigs, cattle, and sheep. During large-scale, standardized breeding, the selective breeding of good livestock breeds hinges on the accurate measurement of body parameters for live animals [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%